THE ROLE OF ORGANIZATIONAL SUPPORT ON NURSING DEVELOPMENT IN SAUDI ARABIAN: A SYSTEMATIC REVIEW - Salah Khlief S. Almotairi (Riyadh First Health Cluster), Saleh Ishq Z Aladhyani (Riyadh Third Health Cluster), Saad Hamdan Alotaibi (Riyadh Third Health Cluster); Yousef Ashaq ZAlodhiyany(Riyadh Third Health Cluster),Fahad Mushabbab S. Alqahtani(Riyadh First Health Cluster), Asia Ali Alahmari(Huraymila General Hospital) (Journal of International Crisis and Risk Communication Research, 2024)
This study aims to explore the impact of organizational support on the professional development of nurses in Saudi Arabia, with a particular focus on how training programs and leadership styles enhance nurses' self-efficacy and innovation. The goal is to highlight strategies that strengthen nursing practices and improve patient outcomes through organizational and training support.This review aims to systematically explore the impact of organizational support on nursing development within healthcare settings in Saudi Arabia. By examining existing studies, this review seeks to identify specific forms of organizational support that enhance nursing competencies, professional growth, and overall job satisfaction among nurses in the region.This systematic review examines the impact of organizational support and training self-efficacy on the development of nursing professionals in Saudi Arabia's healthcare sector. A comprehensive analysis was conducted using the PRISMA flowchart and an integrative approach, evaluating 117 studies published since 2010. The review highlights how training programs, leadership styles, and perceived organizational support influence nurses' self-efficacy, creativity, and overall professional development. Key findings reveal that training positively impacts knowledge, attitudes, and skill development, but challenges persist in translating this training into practice. In Saudi Arabia, there is a growing focus on improving healthcare quality through continuous professional development and support, although barriers such as overwork and limited opportunities for skill application remain significant. The review underscores the importance of tailored training programs and leadership initiatives that foster creativity, self-efficacy, and innovative behaviors among nurses. Ultimately, the study calls for enhanced organizational support mechanisms to better facilitate the integration of skills into daily nursing practices and improve patient outcomes.